2011
DOI: 10.1007/s11829-011-9152-5
|View full text |Cite
|
Sign up to set email alerts
|

Russian wheat aphid (Hemiptera: Aphididae) reproduction and development on five noncultivated grass hosts

Abstract: The Russian wheat aphid, Diuraphis noxia (Kurdjumov), is a small grains pest of worldwide economic importance. The Russian wheat aphid is polyphagous and may encounter differential selective pressures from noncultivated grass hosts. Aphid biotypic diversity can disrupt the progress of plant breeding programs, leading to a decreased ability to manage this pest. The goal of this research was to quantify Russian wheat aphid biotype 2 (RWA2) reproductive and development rates on five common noncultivated grass hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several factors can influence the resistance to high temperatures, including the pattern of temperature fluctuations, genetic lineage, stage of life history, acclimatization, and bacterial symbionts (BOWLER;TERBLANCHE, 2008;PUCHERELLI et al, 2012). Considering that CHEN et al (2013) worked with aphids collected in Taichung, Taiwan, and ZHAOZHI et al (2016) studied aphids collected in Xinjiang, China, it is possible that there are differences between the populations of A. craccivora tested by these authors and the population investigated in this study, mainly regarding genetic lineage, acclimatization, and bacterial symbionts.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors can influence the resistance to high temperatures, including the pattern of temperature fluctuations, genetic lineage, stage of life history, acclimatization, and bacterial symbionts (BOWLER;TERBLANCHE, 2008;PUCHERELLI et al, 2012). Considering that CHEN et al (2013) worked with aphids collected in Taichung, Taiwan, and ZHAOZHI et al (2016) studied aphids collected in Xinjiang, China, it is possible that there are differences between the populations of A. craccivora tested by these authors and the population investigated in this study, mainly regarding genetic lineage, acclimatization, and bacterial symbionts.…”
Section: Resultsmentioning
confidence: 99%
“…Alternate hosts that aphids feed on may impose more selective pressure than wheat does, thereby selecting for biotypes that can better use host plants (Anstead et al 2003). Porter et al (1997) also suggested that noncultivated hosts could be a reservoir for aphid biotypes, and Pucherelli et al (2011) found that Russian wheat aphid could use alternate hosts as population sources throughout the oversummering period and selection pressures are likely high in these hosts, indicating the possibility for selection of biotypes that are potentially virulent to winter wheat. The reproductive and development success of Russian wheat aphid in an area will determine the overall success of the population in the speciÞc area.…”
Section: Resultsmentioning
confidence: 99%
“…The morphological barrier expressed in the ear structure is the main resistance barrier for spring wheat. A high spike density maintains a more resistant grain to aphids (Pucherelli et al, 2012). We assessed the resistance of varieties to aphids (Schizaphis graminum) by the number of inhabited varieties, as well as by the number and size of necrotic spots on the flag leaf of plants.…”
Section: Discussionmentioning
confidence: 99%